Firm characteristics and voluntary disclosure of non-financial and strategic information. - Ng, Alicia Shan Shan. (2008)
This paper examines how various firm characteristics affect the voluntary disclosure of non-financial and strategic information of publicly listed companies incorporated in Singapore. Eleven firm characteristics were being analyzed, namely, firm size, asset structure, financial leverage, industry, auditor, outside directors, profitability, listing status, ownership diffusion, growth and growth potential.